2023
DOI: 10.1111/jebm.12525
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of COVID‐19 vaccination: A systematic review

Abstract: Objective The COVID‐19 vaccination strategy has been widely used to protect population health worldwide. This study aims to summarize the cost‐effectiveness evidence of economic evaluation of COVID‐19 vaccination strategies to provide evidence supporting the usage of COVID‐19 vaccination, especially where the supply of COVID‐19 vaccine is limited. Methods A systematic literature review was performed by searching both English and Chinese databases, including PubMed, Embase, Science Direct, Web of Science, Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Overall, we have demonstrated that vaccination with the Moderna updated COVID-19 vaccine represents a cost-saving measure from both a healthcare payer and a societal perspective compared with no vaccination. This finding is consistent with systematic literature reviews of economic evaluations of COVID-19 vaccination strategies, which provide evidence that COVID-19 vaccination strategies are economically favourable [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
“…Overall, we have demonstrated that vaccination with the Moderna updated COVID-19 vaccine represents a cost-saving measure from both a healthcare payer and a societal perspective compared with no vaccination. This finding is consistent with systematic literature reviews of economic evaluations of COVID-19 vaccination strategies, which provide evidence that COVID-19 vaccination strategies are economically favourable [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are comparable to similar studies, although there have been a limited number of studies published on the cost-effectiveness of oral antivirals or booster doses in low- and middle-income countries. A recent systematic review on the cost-effectiveness of COVID-19 vaccines noted a gap in published literature on the cost-effectiveness of booster doses [58] (June 2023). Our results align with available studies which demonstrate that booster doses appear cost saving in middle and high-income settings [5961].…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, vaccination against COVID-19 has been shown to be cost effective and reduce burden to the health care system. 22 Ensuring sufficient vaccine coverage for both COVID-19 and influenza is a crucial driver to reduce the burden to health care system of significant respiratory illnesses. Improvement in vaccination coverage and likelihood of completing all recommended vaccinations through use of a multi-component, combination vaccine was previously demonstrated in pediatric space.…”
Section: Ethics Reviewmentioning
confidence: 99%